RELASI ANTARA ISRAEL ALKITABIAH DAN NEGARA ISRAEL MODERN PERSPEKTIF GEREJA KATOLIK - Indra Tanureja (Jurnal Teologi (Journal of Theology), 2016)
Israeli Palestinian conflict which is one of the hot issues in our present world, is a particular problem that has both political and religious dimensions. This problem often compels Christians to think about their stand in dealing with the State of Israel. In order to take a proper position, one has to understand the relationship between Biblical Israel and the modern State of Israel. It has to be realized, however, that how one defines the relationship between these two entities depends actually on the interpretive methods that are chosen and applied upon the biblical texts. And because there are many methods of interpreting the biblical texts, it is almost impossible to attain any definitive idea that would be acceptable to all. The Catholics, however, could hold on the Church official teaching on the relationship between the Church and the State of Israel as it is revealed in the official documents published by the Catholic